ANALISIS PERKANDUNGAN EFISIENSI PEMBANGKIT LISTRIK GENERATOR BERBAHAN BAKAR PROPANA (GAS LPG) DAN BENSIN - Imam Wibowo; Raden Bagus Suryasa; Tri Santoso (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
At present around the world, including Indonesia experiencing electrical energy crisis, so that therotating power blackouts. The role of the generator becomes a solution as a backup of energysources. Generators using gasoline and gas as a source of energy. The gas can be LPG (LiquiefiedNatural Gas), Natural Gas, or CNG (Compressed Natural Gas). The method used is usingexperimental methods and theoretically mathematical calculations. In practice, three experimentalspecimens were performed using premium gasoline-fuel converter kits, then with the use of LPGgas fuel converter kits and with the use of premium gasoline fuel carburetors. From these threeexperiments, there are variations of engine rotation, ie normal speed, medium speed, and highspeed speed. From the test results, with the normal speed of engine efficiency generated by theexperiment using a gasoline kit converter produce 34.86% with 3187 rpm engine speed, with LPGgas fuel kit converter produce 46.18% with 3103 rpm engine speed, and by using standard fuelcarburetor gasoline generate 32.02% debgan engine speed 3326 rpm.